Synthesis, characterization, and biological evaluation of organotin(IV) complexes derived from Schiff bases of 3-methoxybenzohydrazide. (1st February 2023) - Pachwania, Sushila; Devi, Jai; Taxak, Bharti; Boora, Ankit
Abstract: New diorganotin(IV) complexes (R2 SnL, where R is Me, Et, Bu, and Ph) of Schiff base ligands N'-(2-hydroxybenzylidene)-3-methoxybenzohydrazide (H2 L 1 ), N'-(5-chloro-2-hydroxybenzylidene)-3-methoxybenzohydrazide (H2 L 2 ), N'-(2-hydroxy-5-nitrobenzylidene)-3-methoxybenzohydrazide (H2 L 3 ), and N'-(4-(diethylamino)-2-hydroxybenzylidene)-3-methoxybenzohydrazidefrom (H2 L 4 ) derived from 3-methoxybenzohydrazide with salicylaldehyde and its derivatives were synthesized. The ligands and their metal complexes were structurally characterized by spectroscopic techniques (FT-IR, 1 H, 13 C, and 119 Sn NMR), elemental analysis, mass spectrometry, melting point, and molar conductance studies. The spectral data showed that ligands are coordinated to the tin atom in a tridentate manner with N and O donor sites of the azomethine-N, enolic-O, and aromatic hydroxyl-O to form a penta-coordinated geometry around central tin atom. The molar conductance data revealed that all compounds are non-electrolytes. In vitro antimicrobial activities of compounds were determined against various pathogens with reference to standard antibiotics which showed that compounds (12 ) (Ph2 SnL 2 ) and (16 ) (Ph2 SnL 3 ) are the most potent antimicrobial agents. Furthermore, the compounds were evaluated for antioxidant activity by using DPPH assay. The results obtained emphasized that the phenyl derivatives of complexes have enhanced antimicrobial and antioxidant activities as compared to other complexes. To check the drug-likeness, in silico studies of the synthesized compounds were carried out which described that all the compounds except (12 ) (Ph2 SnL 2 ), (19 ) (Bu2 SnL 4 ), and (20 ) (Ph2 SnL 4 ) can be used as orally active drugs. Graphical Abstract: UF0001